Susceptibility to PNU-140690 (Tipranavir) of Human Immunodeficiency Virus Type 1 Isolates Derived from Patients with Multidrug Resistance to Other Protease Inhibitors - Rusconi, Stefano (American Society for Microbiology, 2000)
In our study we examined the anti-human immunodeficiency virus type 1 (anti-HIV-1) activity of a novel HIV-1 protease inhibitor, PNU-140690 (tipranavir), against patient-derived isolates resistant to multiple other protease inhibitors (PIs). The aim of our experiments was to investigate the genotypes and the in vitro phenotypes of drug resistance of PNU-140690. We carried out drug susceptibility tests with peripheral blood mononuclear cells and a fixed amount of infectious virus (1,000 50% tissue culture infective doses) to determine the 50% inhibitory concentration (IC(50)) and IC(90), PCR assays for the detection of drug resistance mutations in RNA in plasma, and direct sequencing of PCR products. Phenotypic resistance to PIs was invariably related to genotypic mutations. The substitutions among the amino acid residues of the protease included L10I, K20R, L24I, M36I, N37D, G48V, I54V, L63P, I64V, A71V, V77I, V82A, I84V, and L90M. Isolates from all of the patients had developed a maximal degree of resistance to indinavir, ritonavir, and nelfinavir (IC(50)s, >0.1 μM). We also compared these mutations with the amino acid changes previously described in association with in vivo tipranavir administration. The mutations included the following: I15V, E35D, N37D, R41K, D60E, and A71T. Infections with IIIB, 14aPre, and N70 were inhibited by an average drug IC(90) of 0.18 ± 0.02 μM in multiple experiments. The average mean ± standard error of mean IC(90) for the entire group of multidrug-resistant isolates derived from the mean values for two culture wells with p24 antigen supernatant appeared to be 0.619 ± 0.055 μM (range, 0.31 to 0.86 μM). Tipranavir retained a sustained antiviral activity against PI-MDR clinical isolates and might be useful in combination regimens with other antiretroviral agents for patients who have already failed other PI-containing therapies.